Answers

2015-06-21T21:23:35+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
6x+1+ \frac{1}{3} =x- \frac{3}{6}  \\ 6x+ \frac{4}{3} = x- \frac{3}{6} \\ 5x = -( \frac{4}{3} + \frac{3}{6}) \\ 5x =  -\frac{11}{6}   \\ x=- \frac{11}{30}
0
2015-06-21T21:24:58+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
If the question was:
6x+1+ \frac{1}{3} =x- \frac{3}{6}
6x+ \frac{4}{3} =x- \frac{1}{2}
6x-x= \frac{4}{3} +  \frac{1}{2}
5x= \frac{8+3}{6}
x= \frac{11}{5*6} = \frac{11}{30} .


If the question was:
 \frac{6x+1+1}{3}= \frac{x-3}{6}
2(6x+2)=x-6
12x-4=x-6
11x=2  and x= \frac{2}{11} .
1 5 1
Thank you so much
your welcome
Please mark it as the best
Click on the yellow button below my ans
Sorry the answer will be -11/30 in the first part as it is -4/3-1/2 and i have done 4/3+1/2